Evaluation of antimicrobial and cytotoxic activities of commercial Lactobacillus acidophilus against foodborne pathogens and the MCF-7 cell line - Sundramurthy, Venkatesa Prabhu; Sasidharan Satheesh Kumar; Ragunathan, Ramachandra; Madhusree; Lochana Devi. P (Journal of Applied Pharmaceutical Research, 2025)
Background: Lactobacillus acidophilus, a key member of the lactic acid bacteria (LAB) group, contributes significantly to both human and animal health by enhancing the microbiome. This study explores the bioactive compounds produced by L. acidophilus isolated from the Synkromax probiotic, with a focus on their antimicrobial, antifungal, and anticancer properties. Methodology: The cell-free supernatant (CFS) of L. acidophilus was subjected to solvent extraction to isolate secondary metabolites, while peptides, including bacteriocins, were partially purified using ammonium sulfate precipitation. Metabolite profiling was conducted using Gas Chromatography-Mass Spectrometry (GC-MS/MS), and Thin Layer Chromatography (TLC) was used for qualitative analysis. The antimicrobial and antifungal activities of the extracts were evaluated using the well diffusion method against pathogens, including Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Aspergillus niger, and Aspergillus flavus. The cytotoxic potential of the partially purified bacteriocin extract (PPBE) was assessed using the MTT assay on MCF-7 breast cancer cells. Results and Discussion: GC-MS/MS analysis identified a diverse range of bioactive secondary metabolites. Both CFS and partially purified peptides demonstrated significant antimicrobial and antifungal activity. The PPBE also exhibited strong cytotoxicity against MCF-7 cells, with an IC₅₀ value of 72.3991 µg/mL, indicating promising anticancer potential. Conclusion: Lactobacillus acidophilus from Synkromax produces a variety of bioactive compounds with potent antimicrobial, antifungal, and anticancer activities. These findings support its potential application in therapeutic development and enhancing food safety.